2008
DOI: 10.1007/s00264-008-0577-0
|View full text |Cite
|
Sign up to set email alerts
|

Leg axis correction with ConforMIS iForma™ (interpositional device) in unicompartmental arthritis of the knee

Abstract: Degeneration of the meniscus and the articular cartilage in unicompartmental osteoarthritis of the knee results in progressive deformity of the leg axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
(23 reference statements)
0
13
0
1
Order By: Relevance
“…Comparative positive results including durable and reliable short-term to mid-term results, even through a medial approach after a mean follow-up time of 5 years, were also shown by another group [23,24]. Current trends in new technologies with use of custom-made interpositional devices or custommade lateral unicompartmental knee replacement also seem to show promising results; however, long-term studies are not yet available [25].…”
Section: Discussionmentioning
confidence: 91%
“…Comparative positive results including durable and reliable short-term to mid-term results, even through a medial approach after a mean follow-up time of 5 years, were also shown by another group [23,24]. Current trends in new technologies with use of custom-made interpositional devices or custommade lateral unicompartmental knee replacement also seem to show promising results; however, long-term studies are not yet available [25].…”
Section: Discussionmentioning
confidence: 91%
“…Hemiarthroplasty with metallic interpositional devices, while first described over half a century ago, is also currently experiencing a renaissance as a treatment option for varus unicompartmental OA, the idea being to provide a means of [15]; there are still few reports examining the use of the self-centering UniSpacer™ device in medial gonarthrosis. This study is the first to evaluate clinical and functional results after a minimum follow-up time of five years.…”
Section: Discussionmentioning
confidence: 99%
“…There are almost no data for interpositional hemiarthroplasty. The study by Koeck et al on the iForma™ implant [15] showed an average postoperative alignment (mTFA) of −0.9°and a mean correction of 3.8°. A significant correlation between extent of correction and thickness of the implant was shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adverse outcomes have been reported with the re-established interpositional Unispacer™ knee system (Zimmer, Inc), with devastating early failure rates ranging between 20 and 30 percent caused mainly by implant dislocation and persistent pain [7][8][9], No clinical results have been reported so far for the iForma™ interpositional device (ConforMIS, Inc, Burlington, MA, USA), which was used in our case and is customized via magnetic resonance imaging (MRI). Only the reliability of leg axis correction in unicompartmental knee arthritis with this device has been demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%